Mechanisms of Imprint Effect on Ferroelectric Thin Films - CHAN, HO-KEI (My University, 2005)
We have developed a single/double layer model to explain horizontal shifting of measured D-E hysteresis loops (imprint) for ferroelectric thin films. Such phenomenon can be explained by considering three mechanisms or their multiple effects: (1) stress induced by film/electrode lattice mismatch or clamping, (2) domain pinning induced by, e.g., oxygen vacancies, or (3) degradation of ferroelectric properties in film/electrode surface layers. First, it is found that hysteresis loops under the influence of stress exhibit large horizontal shifts with magnitudes comparable to those observed in experiments. Second, a pseudo-non-switching layer with a large coercive field is assumed to be present at the film/electrode interface in an otherwise homogeneous ferroelectric thin film, and in this case our simulation also shows a large imprint effect. Third, it is also found that time-dependent space-charge-limited conduction is likely to be one origin for the occurrence of imprint.
PUBLISHED
This paper shows that the time-dependent space-charge-limited conduction model developed originally for the study of polarization offsets in compositionally graded ferroelectrics can also be applied to understand the mechanism of imprint effects in homogeneous ferroelectric films.
Keywords: Physics